PENGARUH KUALITAS PELAYANAN MITRA GO-JEK TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL MEDIASI - Feby Thung (STIE Wiyatamandala, 2019)
This study was conducted aiming to find out how the influence of Go-Jek partner service quality on customer loyalty with customer satisfaction as a mediating variable. In this study data were collected through a distributed questionnaire, and the data collected was analyzed using Structural Equation Modeling - Partial Least Square (SEM-PLS). Based on 90 samples that were successfully collected and tested, the results show that, the quality of service of Go-Jek partners has a positive influence on customer satisfaction. Likewise with customer satisfaction that has a positive influence on customer loyalty. And the quality of service of Go-Jek partners who have an influence on customer loyalty. The results of this study will be explained through the results of the research implications, which are expected for Go-Jek partners to be able to know the points that must be improved in their services.